Identifying useful actions to improve team resilience in information systems projects - Amaral, António (2015)
Due to today's business environment demands organizations need to create teams to perform work in projects, with quality, within time and budget. Therefore, teams play a very important role in the organizational development, by creating conditions that enable to overcome difficulties and to promote the improvement of the organizational overall performance. Hence the relevance of studying the project teams resilience, identifying the actions that can influence the project development and its final outcomes. The resilience of a team can be defined as the team's ability to deal with problems, overcome obstacles, or resist the pressure of adverse situations, without entering into rupture. This research, focused on team resilience, firstly involved a literature review, followed by brainstorming sessions, resulting in a preliminary list of useful actions to improve project team resilience. Then, a survey was administered in order to identify the most useful actions perceived from the identified list. Completed questionnaires were received from 115 team members of information technologies/information systems projects being developed in an academic setting. By identifying the most useful actions perceived, as those having the highest potential for increasing project team resilience, practitioners and organizations can set their priorities towards improving team resilience. The results showed that the top ten list of useful actions identified is composed by very well-known and recognized actions, such as the promotion of collaboration and solidarity among project team members, and the recognition, appreciation and use of the talents and competencies of each team member.